Drie sterren - Van Acker, Achille (S.l : [s.n.])
Bibliotheek Camille Huysmans
Dedicator: Van Acker, Achille, dedicatee: Huysmans, Camille
Met een opdracht van de auteur voor Leo Magits
Nederlands
Monografie
Keywords: poëzie